In-line skating in action - Crossingham, John, 1974-; Rouse, Bonna; Crabtree, Marc (New York : Crabtree Pub. Co., 2003)
Discusses basic movements and techniques of in-line skating, recreational and competitive skating, safety tips, and more.
Includes index.
Includes index.
Keywords: In-line skating -- Juvenile literature; In-line skating